Lectotypification of the name Cistus stipulatus, basyonim of Helianthemum stipulatum (Cistaceae) - Ferrer-Gallego, Pedro Pablo; Boisset, Fernando (Phytotaxa, 2015)
The typification of the name Cistus stipulatus Forsskål (≡ Helianthemum stipulatum (Forsskål) Christensen) is discussed. The designation of the nomenclatural type is based on an assessment of Forsskål’s original material. The name is lectotypified selecting a specimen from the Herbarium Forsskålii in the National Herbarium Copenhagen at C.